194 A multicenter characterization of chronic toxicities following adjuvant anti-PD-1 therapy for high risk resected melanoma. (10th December 2020) - Patrinely, James; Johnson, Rebecca; Lawless, Aleigha; Bhave, Prachi; Sawyers, Amelia; Dimitrova, Maya; Yeohc, Hui; Palmeri, Marisa; Davis, Elizabeth; Rapisuwon, Suthee; Long, Georgina; Haydon, Andrew; et al.
Abstract : Background: Anti-programmed death-1 (anti-PD-1) therapies have improved long-term survival across many advanced cancers. However, chronic immune-related adverse events (irAEs) are not well-defined. We sought to determine the incidence, time-course, spectrum, and predictors of chronic irAEs arising from adjuvant anti-PD-1. Methods: In this retrospective cohort, we analyzed patients from 8 academic medical centers with stage III-IV melanoma treated with anti-PD-1 in the adjuvant setting. Acute and chronic (persisting at least 3 months after therapy cessation) irAEs were characterized by type, time-course, management, and incidence. Results: Among 387 patients, most were male (60.7%) with a median age of 63 years, had cutaneous primaries (85.8%), BRAF/NRAS WT (51.2%), and resected stage IIIb (33.1%) or IIIc (39.5%) melanomas. Median overall survival and relapse-free survival (RFS) were not reached. 359 patients (93.0%) were alive at median follow-up of 529 days. Patients with acute (p<0.009) or chronic (p<0.001) irAEs had superior RFS compared with patients lacking irAEs. Treatment was discontinued for therapy completion (50.0%), irAEs (25.3%), and disease progression (20.9%). 267 patients (69.0%) had any acute irAE, including 19.5% (n=52) with grade 3–5 events. Acute irAEs were most commonly dermatitis/pruritis (25.8%), thyroiditis/hypothyroid (16.3%), arthralgias (10.6%), colitis/diarrhea (9.8%) and required glucocorticoids in 109 patients (28.2%). Of these, 167 patients (43.2%) developed chronic irAEs; 82 (49.1%) were symptomatic, 55 (32.9%) required glucocorticoids, and most were grade 1–2 (96.4%). Endocrinopathies (73/88, 83.0%) arthritis (22/45, 48.9%), xerostomia (9/17, 52.9%), neurotoxicities (8/8, 100.0%), and ocular events (5/8, 63.0%) were likely to become chronic events. In contrast, colitis (6/44, 13.6%), hepatitis (4/25, 16.0%), pneumonitis (6/18, 33.3%) were less likely to become chronic. Overall, the most common chronic irAEs were hypothyroidism (14.0%), dermatitis/pruritis (6.6%) arthralgias (5.7%), adrenal insufficiency (3.1%), and xerostomia (2.3%). Age (p=0.67), gender (p=0.31), time of onset of acute irAEs (p=0.95), and initial need for glucocorticoids (p=0.15) were not associated with chronicity. Only 24 (14.4%) of chronic irAEs ultimately resolved during the median 529-day follow-up. In particular, endocrinopathies (100%) arthralgias (100%) ocular events (100%), xerostomia (88.9%), and cutaneous events (89.5%) had high rates of persistence at last follow-up. Conclusions: Chronic irAEs to anti-PD-1 were more common than previously recognized and frequently persisted even with prolonged follow-up, although most were low-grade. The risks of chronic toxic effects should be integrated into treatment decision making. Ethics Approval: This study was approved by the Vanderbilt Institutional Review Board